« ça suffit comme ça ! ». La fausse opposition quantitatif / qualitatif à l’épreuve du discours sarkozyste - Damon Mayaffre (Corela)
Logometry's intent is to take the full measure of discourse through the coordination of quantitative and qualitative explorations into explicit interpretative pathways. Herein, we illustrate the theoretical paradigm of the method through the step-by-step case study of the use of the neutral demonstrative pronoun in french presidential discourse.